Characteristics of Teacher Leaders for Information and Communication Technology - Riel, Margaret; Becker, Henry Jay (International Handbook of Information Technology in Primary and Secondary Education, 2008)
This chapter presents a typology of four dimensions of teacher leadership-a disposition to continually learn from and improve practice, collaboration with peers through critical examination and evolution of each other&s teaching, participation in geographically diverse communities of practice, and making professional contributions through speaking, writing, and teaching. Teacher leadership, from this perspective, is inherently grounded in professional engagement, which in turn is linked with constructivist teaching philosophies and teaching practice and exemplary use of computers. The chapter then summarizes several studies of leadership among technology-expert teachers and applies the more general leadership typology to the specific domain of information and communication technologies-adaptive expertise with respect to technology tools and resources; collaboration around technology; interpersonal networking in technology-active communities; and contributions through organizations to share knowledge about how technology is best used in teaching. The chapter concludes by pointing to several ways that technology leadership might be fostered.
Keywords: TICE; numérique